Fiscal Revenue and Inflationary Finance - Choudhry, Nurun (IMF Working Papers; Working Paper ;, 1990)
This paper analyzes the erosion of fiscal revenue by inflation resulting from the issuance of money. The empirical evidence for a number of developing countries supports the well-known hypothesis that an increase in inflation will result in a fall in real fiscal revenue because of collection lags, thereby possibly widening the fiscal deficit. As such, attempts to generate resources to finance government expenditures via the inflation tax will involve a loss in other revenues, making this form of taxation even less desirable.